Degradable and anti-adhesion artificially synthesized dura mater (spinal mater) patch and preparation method thereof

By adopting a bilayer structure artificially synthesized dura (spine) membrane patch, the problems of non-degradation and inflammatory response of existing materials are solved, effective repair of dura and preventing complications, and flexible, mechanical properties and degradable properties are achieved.

CN119818723APending Publication Date: 2025-04-15西安蝾螈生物技术有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510023517.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing dura repair materials have problems such as non-degradable, leading to inflammatory responses and limited sources, making it difficult to effectively repair dura defects and prevent complications.

Method used

Artificial synthetic dura (spine) membrane patches using a bilayer structure. The rough layer is prepared by electrospinning to promote the regeneration of autologous dura cells. The smooth layer is made of hydrogel to prevent cerebrospinal fluid leakage and adhesion, and has anti-adhesion and biodegradable properties.

Benefits of technology

The flexibility and mechanical properties of the double-layer dura patch are achieved, which significantly promotes the regeneration of damaged meninges, has anti-adhesion and degradability characteristics, is easy to store and prepare, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005232078850000011
    Figure HDA0005232078850000011
  • Figure HDA0005232078850000012
    Figure HDA0005232078850000012
  • Figure HDA0005232078850000013
    Figure HDA0005232078850000013
Patent Text Reader

Abstract

The invention provides a degradable and anti-adhesion artificially synthesized dura mater (spinal mater) patch and a preparation method thereof. The method is relatively simple in process and relatively high in preparation efficiency, the product has a natural three-dimensional structure similar to collagen, and the obtained patch has a double-layer structure, excellent mechanical properties and biocompatibility, can remarkably promote regeneration of damaged meninx tissues, has anti-adhesion and biodegradable properties, and is easy to store, disinfect and prepare before an operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a degradable, anti-adhesion artificial synthetic dura mater patch and a preparation method thereof. Background Art

[0002] The dura mater, also known as the dura mater, is a continuous collagen sheet composed of fibrous tissue surrounding the intracranial and spinal nerve structures. It is the outermost meninges surrounding the central nervous system, providing effective protection for the central nervous system and preventing infection or trauma to the skull and spine. Dura mater defects can lead to continuous leakage of cerebrospinal fluid, which may cause complications such as intracranial infection, encephalocele and epilepsy, and even endanger the patient's life. In addition, the human dura mater is a highly innervated and vascularized membrane, and its vascular system plays a vital role in various diseases such as dural hematoma and meningitis. However, in recent years, incidents of dura mater trauma caused by accidental trauma, tumor resection and craniotomy have continued to occur, and the frequency of occurrence has also increased year by year. Therefore, finding effective dura mater repair materials and improving the repair effect of dura mater trauma is one of the important research directions in the current medical field. Dura mater repair materials play an important role in reconstructing the integrity of the dura mater, protecting brain tissue, and preventing complications such as cerebrospinal fluid leakage, intracranial infection, encephalocele and epilepsy.

[0003] In recent decades, with the development of regenerative medicine, neurosurgeons have developed many different types of dura mater repair materials. At present, the materials used for dura mater repair include autologous tissue, allogeneic materials, xenogeneic materials, synthetic materials and natural materials. Autologous fascia tissue has the advantages of good biocompatibility and no immune rejection, but it needs to be extracted from other parts of the body through surgery, the source is relatively limited, and it may cause other trauma; allogeneic tissue is mostly freeze-dried human dura mater, which has the microstructure of normal human dura mater and can support and protect brain tissue, but the source of materials is limited and has a potential risk of viral infection, which may cause Creutzfeldt-Jakob disease. However, due to limited sources, difficulty in obtaining materials, complex surgical operations and potential viral risks, the above two materials have begun to slowly withdraw from the stage of dura mater repair materials. Xenogeneic materials include bovine membrane, porcine membrane and amniotic membrane, which have certain stretchability and elasticity, can completely repair the dura mater and prevent cerebrospinal fluid leakage. Costa et al.'s study showed that the new bovine collagen membrane material has the effect of preventing cerebrospinal fluid leakage for dura mater repair, which solves the problem of limited sources of autologous tissue repair materials and allogeneic repair materials to a certain extent. However, this type of heterologous material has certain rejection, may cause foreign body reaction, and is difficult to trace; as recorded in patent documents with publication numbers CN112915260, CN110327135, CN1037275 or CN111110920. Artificial synthetic materials are mainly obtained through synthetic polymer processing, with advantages such as abundant sources, low prices and excellent mechanical properties. In 1990, Sakas et al. conducted animal experiments to study the repair effect of dura mater plants made of polyurethane polymers. Although the dura mater has certain sealing properties, it has problems such as non-degradability and inflammatory reactions, as recorded in the patent application with patent publication number CN107596448. Summary of the invention

[0004] The purpose of the present invention is to provide a degradable, anti-adhesion artificial synthetic dura mater patch, which has a double-layer structure, good flexibility, good mechanical properties and good tissue compatibility, can significantly promote the regeneration of damaged meningeal tissue, has anti-adhesion and biodegradable properties, and is easy to store.

[0005] To achieve the above-mentioned object, the present invention provides a degradable, anti-adhesion artificial dura mater patch, which has a double-layer structure, including a rough surface and a smooth surface;

[0006] The rough layer where the rough surface is located is prepared by electrospinning, and when in use, it faces the skull side, and is used to support the growth, migration, proliferation and differentiation of autologous dura mater cells, promote the regeneration of autologous dura mater, and produce a tissue adhesion effect after water absorption and gelation to improve the sealing density;

[0007] The smooth layer where the smooth surface is located is cross-linked and fixed on the rough layer. When in use, it faces the brain tissue side and is used to prevent cerebrospinal fluid leakage and brain tissue adhesion, and can be sutured.

[0008] Furthermore, the rough layer is prepared by preparing spinning solutions of aliphatic polyester and polyester ether respectively and then blending them through electrostatic spinning.

[0009] Furthermore, aliphatic polyesters include polyglycolic acid, polylactic acid, polycaprolactone, polyvalerolactone and copolymers thereof;

[0010] The polyester ethers include poly-1,4-dioxanone-2-one, poly-1,5-dioxepan-2-one, ethylene glycol-aliphatic polyester copolymers and propylene glycol-aliphatic polyester copolymers.

[0011] Furthermore, the rough layer is prepared from a polylactic acid / polycaprolactone copolymer in a mass ratio of (90-50):(10-50).

[0012] Furthermore, the concentration of the spinning solution of polylactic acid is in the range of 8 to 20 wt %, and the concentration of the spinning solution of polycaprolactone is in the range of 2 to 8 wt %.

[0013] Furthermore, the smooth layer is a hydrogel made by mixing chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in a mass ratio of (50-60): (20-30): (5-10): (15-20), and then evenly applied on the prepared rough layer by a hydrogel paint method.

[0014] Furthermore, the mass fraction of chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in the hydrogel is 2.5-5.0wt%.

[0015] Furthermore, a method for preparing a degradable, anti-adhesion double-layer dura mater patch is provided, comprising:

[0016] Preparation of rough layer by electrospinning:

[0017] Prepare a polylactic acid PLA electrospinning solution and a polycaprolactone PCL electrospinning solution with acetone as solvent and concentrations of 8wt% to 10wt% and 2.5wt% to 8wt%, respectively, add the polylactic acid PLA electrospinning solution and the polycaprolactone PCL electrospinning solution into a 10-30ml syringe respectively under a sterile environment, use a 20-22 spinning needle, adjust the voltage to 4-16kV, the flow rate to 0.1-0.3ml / h, the receiving distance to 4cm to 6cm, and the disc receiving tangential rate to 5.2m / s to 9.4m / s. Under these conditions, the mixed fiber of polylactic acid PLA and polycaprolactone PCL prepared has a uniform morphology, no beads and no droplets, and the average diameter of the mixed fiber is 568nm to 699nm, and the diameter distribution is narrow;

[0018] Hydrogel lacquer method to prepare a smooth layer on a rough layer:

[0019] The deacetylation degree is 70% and the molecular weight is 0.85×10 6 Da chitosan powder is added into acetic acid solution with a volume concentration of 2% to 5%, and dissolved by stirring at room temperature to obtain 1.5wt% to 2.75wt% chitosan acetic acid solution;

[0020] Chitosan, bacterial cellulose, tannic acid and sodium hyaluronate are added in a mass ratio of (50-60): (20-30): (5-10): (15-20) respectively, stirred evenly, filtered to remove undissolved impurities, and vacuum degassed until no bubbles are generated within 2 minutes to obtain a 2.5wt%-5.0wt% chitosan / bacterial cellulose / tannic acid / sodium hyaluronate mixed solution;

[0021] The obtained mixed solution is applied on the rough layer to ensure that the coating surface is smooth and flat, and the thickness is consistently maintained at 0.3-0.7 mm at all locations. After cross-linking, it is placed in a vacuum drying oven on a smooth stainless steel plate and dried. The formed double-layer membrane inner package is sterilized by gamma ray irradiation.

[0022] Furthermore, before applying to the rough layer, a 2% genipin solution is added at a volume ratio of 1:1 at room temperature, the solvent is a PBS buffer solution with a pH of 1.2, and the mixture is rapidly stirred for 3 minutes, and then evenly applied to the rough layer after degassing; crosslinking is performed at 37°C for 24 hours; the vacuum degree of vacuum drying is 10Pa, the drying temperature is 50°C, and the drying time is 8 hours;

[0023] or,

[0024] Add 0.58% EDC·HCl and 0.06% NHS solid powder to the mixed solution, stir until completely dissolved, vacuum degassing until no bubbles are generated within 2 minutes, and then evenly apply it on the rough layer; stand for crosslinking at room temperature for 6 hours, place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 10Pa, drying temperature: 40°C, dry for 3 hours, then use 20 times the amount of purified water at 30°C, 110rpm shaking to wash 3 times, each time after 10 minutes, then place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 15Pa, drying temperature: 50°C, and dry for 6 hours.

[0025] Furthermore, the crosslinking is carried out at normal pressure and a high temperature of 105°C for 1 minute, and the vacuum degree of vacuum drying is 10Pa, the drying temperature is 50°C, and the drying time is 8 hours.

[0026] The beneficial effects of the present invention are as follows: the degradable, anti-adhesion artificial dura mater patch provided by the present invention has a double-layer structure, good flexibility, good mechanical properties and tissue compatibility, can significantly promote the regeneration of damaged meningeal tissue, has anti-adhesion and biodegradable properties, the patch is soft and tough, can be bent, folded, and cut at will, the shape and size are easy to control, and it is easy to store, disinfect and prepare before surgery, and its preparation method is simple and easy, and the manufacturing cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image (500×) of the smooth surface of Example 1.

[0028] Figure 2 This is a scanning electron microscope image (500×) of the rough surface of Example 1.

[0029] Figure 3 This is a scanning electron microscope image (500×) of the smooth surface of Example 2.

[0030] Figure 4 This is a scanning electron microscope image (500×) of the rough surface of Example 2.

[0031] Figure 5 This is a HE staining pathological analysis diagram before the animal experiment in Example 1.

[0032] Figure 6 This is a HE staining pathological analysis diagram after the animal experiment in Example 1.

[0033] Figure 7 It is a schematic diagram of the structure of a degradable, anti-adhesion double-layer dura mater patch. DETAILED DESCRIPTION

[0034] In order to further explain the technical means and effects taken by the present invention to achieve the predetermined purpose, the specific implementation methods, structural features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and embodiments. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be noted that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] In order to achieve the purpose of having a double-layer structure, good flexibility, good mechanical properties and good tissue compatibility, being able to significantly promote the regeneration of damaged meningeal tissue, having anti-adhesion and biodegradable properties, and being easy to store, this embodiment provides a degradable, anti-adhesion artificial dura mater patch, which has Figure 7 The double-layer structure shown includes a rough surface 1 and a smooth surface 2;

[0036] The rough layer where the rough surface is located is prepared by electrospinning, and when in use, it faces the skull side, and is used to support the growth, migration, proliferation and differentiation of autologous dura mater cells, promote the regeneration of autologous dura mater, and produce a tissue adhesion effect after water absorption and gelation to improve the sealing density;

[0037] The smooth layer where the smooth surface is located is cross-linked and fixed on the rough layer. When in use, it faces the brain tissue side and is used to prevent cerebrospinal fluid leakage and brain tissue adhesion, and can be sutured.

[0038] The rough layer is prepared by electrospinning and blending the spinning solutions of aliphatic polyester and polyester ether. In this embodiment, the aliphatic polyester includes polyglycolic acid, polylactic acid, polycaprolactone, polyvalerolactone and copolymers thereof; and the polyester ether includes poly-1,4-dioxanone-2-one, poly-1,5-dioxanone-2-one, ethylene glycol-aliphatic polyester copolymer and propylene glycol-aliphatic polyester copolymer.

[0039] The preferred preparation scheme is that the rough layer is preferably a copolymer of polylactic acid / polycaprolactone because its dynamic properties and degradation rate are easy to control. In the copolymer, the preferred mass ratio of polylactic acid to polycaprolactone is in the range of (90-50): (10-50), which is controlled by adjusting the concentration ranges of the two spinning solutions respectively, for example, the concentration range of the spinning solution of polylactic acid is 8-20wt%, and the concentration of the spinning solution of polycaprolactone is 2-8wt%.

[0040] The smooth layer is a hydrogel made by mixing chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in a mass ratio of (50-60): (20-30): (5-10): (15-20), and then evenly applied on the prepared rough layer by a hydrogel paint method. The preferred scheme is: the mass ratio of chitosan, bacterial cellulose, tannic acid and sodium hyaluronate is 55:20:5:20, and the mass fraction of the mixture prepared by chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in the hydrogel is 2.5-5.0wt%, so that the thickness of the hydrogel coating (thickness of the smooth layer) can be controlled, for example, controlled at 0.1-0.3mm.

[0041] It should be noted that the addition of bacterial cellulose significantly improves the defects of pure chitosan film, which is brittle and easy to curl when exposed to water, and improves the mechanical properties. The addition of tannic acid plays a role in astringency, antibacterial, anti-oxidation and anti-inflammatory, and the addition of sodium hyaluronate can prevent adhesion to a certain extent.

[0042] After forming a hydrogel coating (i.e., a smooth layer) on a blended copolymer microporous matrix layer (i.e., a rough layer) prepared by an electrospinning method by a hydrogel coating method, vacuum low-temperature drying is performed to obtain a double-layer dura mater patch, i.e., a degradable, anti-adhesion synthetic dura mater patch provided in this embodiment, which, in addition to having excellent mechanical properties and biocompatibility, can also promote cell growth and proliferation, is safe, non-immunogenic, and has certain anti-tissue adhesion and biodegradability properties. The preparation method is simple and the cost is low. The patch is soft and tough, can be bent, folded, and cut at will, and the shape and size are easy to control, and it is easy to store, disinfect, and prepare before surgery.

[0043] The above-mentioned degradable and anti-adhesion synthetic dura mater patch is further described below through several specific embodiments.

[0044] Embodiment 1:

[0045] A method for preparing a degradable, anti-adhesion double-layer dura mater patch comprises the following steps:

[0046] 1) Preparation of rough layer by electrospinning

[0047] The solvents of the electrospinning solutions of polylactic acid PLA and polycaprolactone PCL are both acetone, and the solution concentrations are 10wt% and 2.5wt% respectively. The spinning solutions are added to 20ml syringes respectively under a sterile environment, and a 20-gauge needle is used. The voltage is adjusted to 12kV, the flow rate is 0.2ml / h, the receiving distance is 4cm, and the disc receiving tangential rate is 6.8m / s. The PLA and PCL mixed fibers prepared under these conditions have uniform morphology, no beads or droplets, and the average fiber diameter is 568nm with a narrow diameter distribution;

[0048] 2) Hydrogel paint method to prepare a smooth layer on a rough layer

[0049] Chitosan powder (deacetylation degree 70%, molecular weight 0.85×10 6 Da) adding 5% (v / v) acetic acid solution, stirring and dissolving at room temperature to obtain a 2.75wt% chitosan acetic acid solution. Adding bacterial cellulose, tannic acid and sodium hyaluronate in a ratio of 55:20:5:20 respectively, stirring evenly, filtering to remove undissolved impurities, and vacuum degassing until no bubbles are generated within 2 minutes to obtain a 5.0wt% chitosan / bacterial cellulose / tannic acid / sodium hyaluronate mixed solution.

[0050] Add 2% (m / m) genipin solution (PBS pH = 1.4 buffer) at room temperature in a volume ratio of 1:1, stir rapidly for 3 minutes, and evenly apply it on the rough layer of the patch after degassing to ensure that the surface of the sol is smooth and flat, the thickness is consistent everywhere, and it meets the aforementioned preferred thickness range of 0.3-0.7 mm, and crosslink at 37°C for 24 hours. Place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 10Pa, drying temperature: 50°C, and dry for 8 hours.

[0051] The formed double-layer membrane inner package was sterilized by γ-ray irradiation to obtain a degradable, anti-adhesion double-layer dura mater patch. The cross section and smooth layer surface of the sample of Example 1 were observed using a scanning electron microscope. Figure 1 As shown, the smooth layer faces the brain tissue side, has no pores, has a dense structure, and no obvious small clusters or aggregates are seen; Figure 2 As shown, the pore size distribution of the rough layer is between 90 and 200 μm, which is suitable for cell growth and reproduction; the double-layer dura mater patch provided in this embodiment has no excessively large cavities between the layers, and the interlayer materials have good compatibility and good contact. The average thickness of the rough layer of the sample in Example 1 is measured to be 0.393 mm, and the total thickness of the double-layer dura mater patch provided in this embodiment is 0.589 mm.

[0052] The mechanical properties of the sample of Example 1 were measured using an electronic tensile machine, with the stretching and suturing rates set to 100 mm / min and the maximum load of the sensor set to 300 kg. The wet tensile strength of the double-layer dura mater patch provided in this example was 18.5 MPa, the elongation at break was 73.1%, and the suturing strength was 14.6 N. The bursting strength measured by the film pressure rupture strength method was 22.4 kPa.

[0053] Artificial cerebrospinal fluid was used to simulate twice the maximum intracranial pressure (the maximum intracranial pressure in adults is reported to be 5.3 kPa, equivalent to about 1100 mmH 2 O), and the anti-leakage ability of the smooth side of the sample in Example 2 was measured. The double-layer dura mater patch can withstand a static water pressure of 1100 mmH 2 O maintains no leakage within 30 minutes.

[0054] NIH / 3T3 cells were directly cultured on the sample of Example 1, and the cells cultured for 24 hours were tested for in vitro cytotoxicity using the CCK-8 method. It can be seen that the relative proliferation rate of cells in the double-layer dura mater patch provided in this example was 239%, and there was no cytotoxicity.

[0055] Three months after implantation in animals, the smooth layer showed no adhesion, but blood vessels and fibroblasts grew into the rough layer. Figure 5 , 6 It shows that it can play a certain role in preventing adhesion and has good performance in promoting tissue regeneration.

[0056] Embodiment 2:

[0057] A method for preparing a degradable, anti-adhesion double-layer dura mater patch comprises the following steps:

[0058] 1) Preparation of rough layer by electrospinning

[0059] The solvents of the electrospinning solutions of PLA and polycaprolactone PCL are both acetone, and the solution concentrations are 8wt% and 8wt% respectively. The spinning solutions are added to 20ml syringes respectively under a sterile environment, using a 20-gauge needle, a voltage of 16kV, a flow rate of 0.4ml / h, a receiving distance of 6cm, and a disc receiving tangential rate of 9.6m / s. The PLA and PCL hybrid fibers prepared under these conditions have uniform morphology, no beads or droplets, and an average fiber diameter of 699nm with a narrow diameter distribution;

[0060] 2) Hydrogel paint method to prepare a smooth layer on a rough layer

[0061] High molecular weight chitosan powder (deacetylation degree 70%, molecular weight 0.85×10 6 Da) adding 2% (v / v) acetic acid solution, stirring and dissolving at room temperature to obtain a 1.5wt% chitosan acetic acid solution. Adding bacterial cellulose, tannic acid and sodium hyaluronate dispersions in a ratio of 60:5:15:20 respectively, stirring evenly, filtering to remove undissolved impurities, and vacuum degassing until no bubbles are generated within 2 minutes to obtain a 2.5wt% chitosan / bacterial cellulose / tannic acid / sodium hyaluronate mixed solution.

[0062] Then evenly apply it on the rough layer of the patch to ensure that the sol surface is smooth and flat, the thickness is consistent everywhere, and it meets the aforementioned preferred thickness range of 0.3-0.7mm. Place it in a vacuum drying oven on a smooth stainless steel plate, heat crosslink at 105℃ for 1min under normal pressure, adjust the parameters of vacuum degree: 10Pa, drying temperature: 50℃, and dry for 8h.

[0063] The formed double-layer membrane was wrapped and sterilized by γ-ray irradiation to obtain a degradable and anti-adhesion double-layer dura mater patch. The cross section and smooth layer surface of the sample of Example 1 were observed using a scanning electron microscope. Figure 3 As shown, the smooth layer faces the brain tissue side and has a denser structure; Figure 4 As shown, the pore size distribution of the rough layer is between 78 and 235 μm, which is suitable for cell growth and reproduction; there is no excessive cavity between the layers of the double-layer dura mater patch, and the interlayer materials have good compatibility and good contact. The average thickness of the rough layer of the sample in Example 2 is measured to be 0.215 mm, and the total thickness of the double-layer dura mater patch provided in this example is 0.503 mm.

[0064] The mechanical properties of the sample of Example 2 were measured using an electronic tensile machine, with the stretching and suturing rates set to 100 mm / min and the maximum load of the sensor set to 300 kg. The wet tensile strength of the double-layer dura mater patch was 16.5 MPa, the elongation at break was 36.1%, and the suturing strength was 13.1 N. The bursting strength was measured using the film pressure rupture strength method and was 18.6 kPa.

[0065] Artificial cerebrospinal fluid was used to simulate twice the maximum intracranial pressure (the maximum intracranial pressure in adults is reported to be 5.3 kPa, equivalent to about 1100 mmH 2 O), and the anti-leakage ability of the smooth layer side of the sample in Example 2 was measured. The double-layer dura mater patch can withstand a static water pressure of 1100 mmH 2 O maintains no leakage within 10 minutes.

[0066] NIH / 3T3 cells were directly cultured on the sample of Example 2, and the cells cultured for 24 hours were tested for in vitro cytotoxicity using the CCK-8 method. The relative cell proliferation rate of the double-layer dura mater patch provided in this example was 251%, and there was no cytotoxicity.

[0067] Embodiment 3:

[0068] A method for preparing a degradable, anti-adhesion double-layer dura mater patch comprises the following steps:

[0069] 1) Preparation of rough layer by electrospinning

[0070] The solvents of the electrospinning solutions of PLA and PCL are both acetone, and the concentrations of the solutions are 9wt% and 4wt%, respectively. The spinning solutions are added to 20ml syringes respectively under a sterile environment, using a 20-gauge needle, a voltage of 14kV, a flow rate of 0.4ml / h, a receiving distance of 4cm, and a disc receiving tangential rate of 8.8m / s. The PLA and PCL hybrid fibers prepared under these conditions have a uniform morphology, no beads or droplets, and a narrow diameter of 596nm;

[0071] 2) Hydrogel paint method to prepare a smooth layer on a rough layer

[0072] High molecular weight chitosan powder (deacetylation degree 80%, molecular weight 1.25×10 5 Da) add 2% (v / v) acetic acid solution, stir and dissolve at room temperature to obtain 1.5wt% chitosan acetic acid solution. Add bacterial cellulose, tannic acid and sodium hyaluronate dispersion in a ratio of 58:22:5:15, stir evenly and filter to remove undissolved impurities to obtain a 2.5wt% chitosan / bacterial cellulose / tannic acid / sodium hyaluronate mixed solution,

[0073] Then add 0.58% (m / m) EDC·HCl and 0.06% (m / m) NHS solid powder, stir until completely dissolved, and vacuum degassing until no bubbles are generated within 2 minutes.

[0074] Apply it evenly on the rough layer of the patch to ensure that the surface of the sol is smooth and flat, the thickness is consistent everywhere, and it meets the aforementioned preferred thickness range of 0.3-0.7mm. Let it stand for crosslinking at room temperature (20°C) for 6 hours. Place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 10Pa, drying temperature: 40°C, and dry for 3 hours. Use 20 times the amount of purified water at 30°C and 110rpm to wash 3 times, each time for 10 minutes, and then place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 15Pa, drying temperature: 50°C, and dry for 6 hours.

[0075] The formed double-layer membrane is wrapped inside and sterilized by γ-ray irradiation to obtain a degradable and anti-adhesion double-layer dura mater patch.

[0076] The mechanical properties of the sample of Example 3 were measured using an electronic tensile machine, with the stretching and suturing rates set to 100 mm / min and the maximum load of the sensor set to 300 kg. The wet tensile strength of the double-layer dura mater patch was 17.9 MPa, the elongation at break was 46.1%, and the suturing strength was 14.2 N. The bursting strength was measured using a thin film compression rupture strength method and was 28.1 kPa.

[0077] Artificial cerebrospinal fluid was used to simulate twice the maximum intracranial pressure (the maximum intracranial pressure in adults is reported to be 5.3 kPa, equivalent to about 1100 mmH 2 O), and the anti-leakage ability of the smooth layer side of the sample of Example 3 was measured. The double-layer dura mater patch provided in this example can withstand a static water pressure of 1100 mmH 2 O maintains no leakage within 30 minutes.

[0078] NIH / 3T3 cells were directly cultured on the sample of Example 3, and the cells cultured for 24 hours were tested for in vitro cytotoxicity using the CCK-8 method. The relative cell proliferation rate of the double-layer dura mater patch provided in this example was 108%, and there was no cytotoxicity.

[0079] The above contents are further detailed descriptions of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can also make several substitutions or modifications to these described embodiments without departing from the concept of the present invention, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention.

Claims

1. A degradable, anti-adhesion synthetic dura mater patch, characterized in that: It has a double-layer structure, including a rough surface and a smooth surface; The rough layer where the rough surface is located is prepared by electrospinning, and when in use, it faces the skull side, and is used to support the growth, migration, proliferation and differentiation of autologous dura mater cells, promote the regeneration of autologous dura mater, and produce a tissue adhesion effect after water absorption and gelation to improve the sealing density; The smooth layer where the smooth surface is located is cross-linked and fixed on the rough layer. When in use, it faces the brain tissue side and is used to prevent cerebrospinal fluid leakage and brain tissue adhesion, and can be sutured.

2. The synthetic dura mater patch according to claim 1, characterized in that: The rough layer is prepared by preparing spinning solutions of aliphatic polyester and polyester ether respectively and then blending them through electrostatic spinning.

3. The synthetic dura mater patch according to claim 2, characterized in that: The aliphatic polyester includes polyglycolic acid, polylactic acid, polycaprolactone, polyvalerolactone and copolymers thereof; The polyester ethers include poly-1,4-dioxanone-2-one, poly-1,5-dioxepan-2-one, ethylene glycol-aliphatic polyester copolymers and propylene glycol-aliphatic polyester copolymers.

4. The synthetic dura mater patch according to claim 3, characterized in that: The rough layer is prepared from a polylactic acid / polycaprolactone copolymer in a mass ratio of (90-50):(10-50).

5. The synthetic dura mater patch according to claim 4, characterized in that: The concentration of the spinning solution of polylactic acid is in the range of 8-20 wt %, and the concentration of the spinning solution of polycaprolactone is in the range of 2-8 wt %.

6. The synthetic dura mater patch according to claim 1, 2, 3, 4 or 5, characterized in that: The smooth layer is a hydrogel prepared by mixing chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in a mass ratio of (50-60): (20-30): (5-10): (15-20), and then evenly smeared on the prepared rough layer by a hydrogel paint method.

7. The synthetic dura mater patch according to claim 6, characterized in that: The mass fraction of chitosan, bacterial cellulose, tannic acid and sodium hyaluronate in the hydrogel is 2.5-5.0wt%.

8. A method for preparing a degradable, anti-adhesion double-layer dura mater patch, characterized in that: include: Preparation of rough layer by electrospinning: Prepare a polylactic acid PLA electrospinning solution and a polycaprolactone PCL electrospinning solution with acetone as solvent and concentrations of 8wt% to 10wt% and 2.5wt% to 8wt%, respectively, add the polylactic acid PLA electrospinning solution and the polycaprolactone PCL electrospinning solution into a 10-30ml syringe respectively under a sterile environment, use a 20-22 spinning needle, adjust the voltage to 4-16kV, the flow rate to 0.1-0.3ml / h, the receiving distance to 4cm to 6cm, and the disc receiving tangential rate to 5.2m / s to 9.4m / s. Under these conditions, the mixed fiber of polylactic acid PLA and polycaprolactone PCL prepared has a uniform morphology, no beads and no droplets, and the average diameter of the mixed fiber is 568nm to 699nm, and the diameter distribution is narrow; Hydrogel lacquer method to produce a smooth layer on a rough layer: The deacetylation degree is 70% and the molecular weight is 0.85×10 6 Da chitosan powder is added into acetic acid solution with a volume concentration of 2% to 5%, and dissolved by stirring at room temperature to obtain 1.5wt% to 2.75wt% chitosan acetic acid solution; Chitosan, bacterial cellulose, tannic acid and sodium hyaluronate are added in a mass ratio of (50-60): (20-30): (5-10): (15-20) respectively, and the mixture is stirred evenly, filtered to remove undissolved impurities, and vacuum degassed until no bubbles are generated within 2 minutes to obtain a mixed solution of 2.5wt% to 5.0wt% chitosan / bacterial cellulose / tannic acid / sodium hyaluronate; The obtained mixed solution is applied on the rough layer to ensure that the coating surface is smooth and flat, and the thickness is consistently maintained at 0.3-0.7 mm at all locations. After cross-linking, it is placed in a vacuum drying oven on a smooth stainless steel plate and dried. The formed double-layer membrane inner package is sterilized by gamma ray irradiation.

9. The preparation method according to claim 8, characterized in that: Before applying the coating to the rough layer, a 2% genipin solution is added at a volume ratio of 1:1 at room temperature, the solvent is a PBS buffer solution with a pH of 1.4, and the solution is rapidly stirred for 3 minutes, and then evenly applied to the rough layer after degassing. Crosslinking was performed by standing at 37°C for 24 hours; vacuum drying was performed at a vacuum degree of 10 Pa, a drying temperature of 50°C, and a drying time of 8 hours; or, Add 0.58% EDC·HCl and 0.06% NHS solid powder to the mixed solution, stir until completely dissolved, vacuum degassing until no bubbles are generated within 2 minutes, and then evenly apply it on the rough layer; stand for crosslinking at room temperature for 6 hours, place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 10Pa, drying temperature: 40°C, dry for 3 hours, then use 20 times the amount of purified water at 30°C, 110rpm shaking to wash 3 times, each time after 10 minutes, then place it in a vacuum drying oven on a smooth stainless steel plate, vacuum degree: 15Pa, drying temperature: 50°C, and dry for 6 hours.

10. The preparation method according to claim 8, characterized in that: The crosslinking is carried out under normal pressure and high temperature heat crosslinking at 105° C. for 1 minute, the vacuum degree of vacuum drying is 10 Pa, the drying temperature is 50° C., and the drying is carried out for 8 hours.

Citation Information

Patent Citations

  • Anti-adhesion membrane adopting double-layer structure and preparation method of anti-adhesion membrane

    CN105194739A

  • Bionical type absorbable dura mater patch and preparation method and application thereof

    CN105999419A

  • Anti-adhesion compound dural patch and preparation method thereof

    CN106901866A

  • Multifunctional dura mater repairing material based on biomimetic design and preparation method thereof

    CN109260520A

  • Degradable and anti-adhesion double-layer dural patch and preparation method thereof

    CN111420123A